Internal Marketing - Case Studies - Jaiswal, K. S.; Saha, Dipti (Indian Journal of Marketing, 2007)
In the present era, it is said that the consumer is the king and all marketing efforts should be directed towards satisfying the consumers. As such even until the past few years, marketing was viewed only as an external oriented concept whereby the focus was the external party, i.e., the consumers. But it has been observed by various researches and investigations that if the internal party, i.e., the EMPLOYEES of an organization are motivated and satisfied only then they can satisfy the consumers effectively.Keeping this basic need in view, a new concept emerged known as 'Internal Marketing' which works on the fundamental principle of "Employees First!" All the strategies, practices, tools and techniques used to satisfy the employees of an organization are known as Internal Marketing. Internal marketing is an ongoing process that occurs strictly within a company or organization whereby the functional process aligns, motivates and empowers employees at all management levels to consistently deliver a satisfying customer experience. Inter Marketing is an important 'implementation tool'. It aids communication and helps us to overcome any resistance to change. It is simple to construct, especially if one is familiar with traditional principles of Marketing. Internal Marketing obeys the same rules and has a similar structure to external marketing. The main differences here are that the customers are the staffs of the organization. The same principles that apply to keeping external customers happy apply to keeping internal customers happy too.